POTENTIAL OF THREE LOCALLY AVAILABLE FERMENTED OIL CAKE PROTEIN AS REPLACEMENT OF GROUNDNUT OIL CAKE PROTEIN IN THE DIET OF ROHU, LABEO ROHITA - Mohanty, S.; CHOUDHURY, D.; SAHU, B.; KUMAR, SHIVENDRA; MOHANTA, K. N.; DAS, S. S.; BARIK, B. (Journal of the Inland Fisheries Society of India, 2026)
The study was carried out to find out the efficacy of three locally available oil cakes namely, sunflower oil cake (SFOC), linseed oil cake (LSOC) and coconut oil cake (COC) in the diet of rohu (Labeo rohita) by replacing groundnut oil cake (GNOC) in a feeding trial of 90 days. Seven iso-nitrogenous (CP 30%) and iso-caloric (365 kcal/100 g feed) experimental diets were formulated by replacing 50% of GNOC protein of the control diet (T0 ) with raw SFOC (T1 ), fermented SFOC (T2 ), raw LSOC (T3 ), fermented LSOC (T4 ), raw COC (T5 ) and fermented COC (T6 ). At the end of the feeding trial a significantly higher (P<0.05) weight gain (294.771±3.771%), daily weight gain (0.202±0.004 g) and specific growth rate (1.526± 0.010 %) were recorded in T4 group. Significantly (P<0.05) lower feed conversion ratio and higher (P<0.05) protein efficiency ratio and protein productive value were also noted in T4 group. The whole body protein content was found significantly (P<0.05) higher in T4 group (68.928±0.090%). Diet T2 resulted in highest reduction in feed cost/ kg weight gain of fish (26.51 %) followed by diet T4 (24.79 %). Hence, 48 h solid state fermented LSOC and SFOC were found to be the promising alternatives to partially replace GNOC in the diets of rohu.